1982
DOI: 10.1002/1097-0142(19821101)50:9<1783::aid-cncr2820500923>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of tumoral markers in serous effusions. Carcinoembryonic antigen, alpha1-acidglycoprotein, alpha-fetoprotein, phosphohexose isomerase, and Beta2-microglobulin

Abstract: In order to discriminate between benign and malignant effusions, the value of carcinoembryonic antigen (CEA), alpha1‐acidglycoprotein (AGP), alpha‐fetoprotein (AFP), phosphohexose isomerase (PHI), and beta2‐microglobulin (B2M) has been estimated in serous effusions in a group of 106 patients, 30 with a malignant and 76 with a benign effusion. Mean CEA and AGP levels in malignant effusions were significantly higher than in benign effusions; no significant differences of mean PHI, AFP and B2M levels of benign an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

1987
1987
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 22 publications
0
8
0
4
Order By: Relevance
“…In fact some studies have concluded that the measurement of ascitic tumour markers does not improve the discriminative ability of malignant effusions. 7,8,15,20 Nevertheless, the present study found that AFP levels were higher in serum than in ascitic fluid and this agrees with the view that AFP levels are always higher in serum than in ascites and are much more sensitive than ascitic cytology in detecting hepatocellular carcinoma. 2 Benign diseases, especially liver cirrhosis, tuberculous peritonitis or nephrotic syndrome have also been the focus for ascitic fluid tumour marker analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact some studies have concluded that the measurement of ascitic tumour markers does not improve the discriminative ability of malignant effusions. 7,8,15,20 Nevertheless, the present study found that AFP levels were higher in serum than in ascitic fluid and this agrees with the view that AFP levels are always higher in serum than in ascites and are much more sensitive than ascitic cytology in detecting hepatocellular carcinoma. 2 Benign diseases, especially liver cirrhosis, tuberculous peritonitis or nephrotic syndrome have also been the focus for ascitic fluid tumour marker analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, complete separation between malignant ascites and nonmalignant ascites has not been always possible. To increase diagnostic efficiency, cytologic evaluation has been coupled with the analysis in both serum and ascitic fluid for total protein [10,11], various enzymes [9], fibronectin [11,12], tumor antigens [13,14], and lipids [15][16][17], etc.…”
Section: Introductionmentioning
confidence: 97%
“…CEA is an oncofetal antigen that increases most frequently in colorectal cancer, and association of its level with tumour stage was shown in lung cancer (3). CEA level increase was shown in 34–88% of the pleural effusion associated with malignancy (2,21). It was stated that the diagnostic value of CEA was especially important in malignancy cases with cytologically negative of pleural effusions (22).…”
Section: Discussionmentioning
confidence: 99%